Factors Affecting Urinary Retention in Patients Undergoing Anterior Cruciate Ligament Repair Surgery - Atungkoon, Dudsadee (Thai Journal of Anesthesiology, 2021)
Background: One of the complications after anterior cruciate ligament repair surgery is urinary retention. It creates a lot of pain and anxiety for the patient. The incidence of urinary retention after anesthesia was approximately 5-70%, which was significantly different due to the patient group and the type of surgery. Objectives: To investigate the incidence and risk factors of urinary retention in patients undergoing anterior cruciate ligament repair surgery. Methods: The retrospective study was performed by reviewing medical records of patients undergoing anterior cruciate ligament repair surgery from December 1, 2014, to December 1, 2019. All data were analyzed by the multiple logistic regression in the SPSS program. Results: From 385 patients undergoing anterior cruciate ligament repair surgery, 84 cases (21.8%) developed postoperative urinary retention. The significant risk factor was the volume of the intravenous fluid equal to or greater than 835 ml (p=0.019). There was no correlation between urinary retention and age, sex, body weight, comorbid disease, duration of surgery, techniques of anesthesia, and the amount of pain medication received. Conclusion: The incidence of postoperative urinary retention in anterior cruciate ligament repair surgery was 21.8%. The significant risk factor was the volume of the intravenous fluid equal to or greater than 835 ml (p=0.019)